Designing of thiazolidinones against chicken pox, monkey pox, and hepatitis viruses: A computational approach. (April 2023) - Raza, Muhammad Asam; Farwa, Umme; Ishaque, Fatima; Al-Sehemi, Abdullah G.
Abstract: Computational designing of four different series (D-G ) of thiazolidinone was done starting from different amines which was further condensed with various aldehydes. These underwent in silico molecular investigations for density functional theory (DFT), molecular docking, and absorption, distribution metabolism, excretion, and toxicity (ADMET) studies. The different electrochemical parameters of the compounds are predicted using quantum mechanical modeling approach with Gaussian. The docking software was used to dock the compounds against choosing PDB file for chickenpox, human immunodeficiency, hepatitis, and monkeypox virus as 1OSN, 1VZV, 6VLK, 1RTD, 3I7H, 3TYV, 4JU3, and 4QWO, respectively. The molecular interactions were visualized with discovery studio and maximum binding affinity was observed with D8 compounds against 4QWO (- 13.383 kcal/mol) while for compound D5 against 1VZV which was −12.713 kcal/mol. Swiss ADME web tool was used to assess the drug-likeness of the designed compounds under consideration, and it is concluded that these molecules had a drug-like structure with almost zero violations. Graphical Abstract: ga1 Highlights: Forty-four Thiazolidinone were proposed theoretically. DFT and Docking studies were conducted with different software against various virus PDB files. ADMET assessment was conducted using online available software. Homology modeling study of the effective proteins was made.